The effect of temperature and storage time of cuccal swabs on FGA and D13S317 loci with the STR PCR method - Masjkur, Indah Nuraini; Arfianti, Evy; Yudianto, Ahmad; Furqoni, Abdul Hadi; Aâ€™yun, Qurrota (Jurnal Teknologi Laboratorium, 2020)
The samples used for forensic DNA analysis in living individuals are usually blood and buccal swabs, however, blood collection requires an invasive method that can cause discomfort, thus a buccal swab can be a good choice for individuals examined, especially children. This study aimed to determine the effect of temperature and storage time of buccal swabs on the quantity of DNA as material for DNA examination in the forensic field. This study was a laboratory experiment to determine the effect after treatment. Buccal swab samples were 48 and divided into 2 temperature groups, namely room temperature (RT) and 4â„ƒ. The division of the temperature groups was also observed with time differences, namely 1, 3, 5, 7 days. EDNA extraction used the DNAzol method and DNA quantification used a Spectrophotometer. The PCR process was carried out with STR primers FGA and D13S317 loci. The visualization stage used acrylamide gel and silver staining. The results of this study prove that there is an effect of temperature and storage time of buccal swab samples. The longer the treatment time, the lower the DNA level. With statistical analysis, it is obtained p-value of <0.005, it can be concluded that there are significant differences in DNA levels at the temperature and storage time treatments of the buccal swab sample. The results of DNA visualization at the FGA and D13S317 loci using the STR PCR method in this study can still be detected and can be used as a reference for examination in forensic cases.